Synthesis, Characterization and Application of Nano-adsorbent Materials in the Sorption of Pb(II), Ni(II), Co(II), Mn(II), Li(I) from Aqueous Solution - Gad, Hamdi Mohamed Hassan; Labib, Sh.; Aly, M. I. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
In this study, nano-adsorbent materials were synthesized from two different precursors by thermal activation technique. The first was the synthesizing of nano-zinc silicate from chemical reagents of zinc oxide and commercial silica gel. The second was the preparation of nano-pore size activated carbon from different biomass. The synthesized nano-adsorbent materials were characterized by different techniques; Surface Area, FTIR, XRD and SEM. The prepared nano-adsorbent materials were applied in the sorption and separation of some heavy metals from aqueous solution. These metals includes; Pb (II), Ni(II), Co(II), Mn(II) and Li(I). Some factors affecting on the sorption process (e.g. contact time and pH) were investigated. It was found that: the nano-zinc silicate (of ratio 1:1 thermally treated at 700 0C) and nano-pores activated carbon (prepared from saw dust impregnated with 70% H3PO4 overnight, then heated to 500 0C in presence of steam for 80 min.) were the best samples for sorption and separation of concerned heavy metals.